Communicative functions and characterization in the Chinese graphic novel adaptations of "Little Women" - Lee, Tzu-yi (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
This article attempts to use an integrated theoretical framework to examine the three graphic novels published in Taiwan based on Louisa May Alcott’s Little Women. After the concept of intertextuality (Kristeva, 1980), Kress and van Leeuwen’s (1996) visual grammar helps us to explore how the visual semiotic resources in three Taiwanese graphic novel editions of Little Women ascribe meanings, achieve functions and communicate ideologies to enhance the characterization of Jo March. Progressing from the images, image–text relationships are discussed in terms of how these signifiers shape signs and meaning. Finally, by exploring speech or thought representation, the researcher investigates the translators’ awareness of the readers and situates their use of signs socially and culturally. In this study, the integrated framework reveals how these semiotic resources characterize Jo March, and the double meanings (Kristeva, 1980, pp. 65–66) they present, differently. These characterisations may, in turn, may have affected the communicative function of each version. The study concludes with a discussion of the strengths and weaknesses of these applications.